Efeitos comportamentais e neuroquímicos de ácido alfa-lipóico e desvenlafaxina em modelo animal de depressão induzido por corticosterona - Sousa, Caren Nádia Soares de (2015)
Depression is a serious and disabling psychiatric disorder that affects people of all socioeconomic classes, ethnicities and ages. Recent studies have suggested a possible involvement of oxidative stress in the pathogenesis of depression and substances with antioxidant potential may be used to treat this disorder. Based on this assumption, the present study investigated the behavioral and neurochemical effects of repeated administration of α-lipoic acid (ALA), alone or associated with desvelafaxine (DVS), in depression model induced by chronic administration of corticosterone (CORT). Swiss female mice (25-30g) were used and these were given subcutaneously, vehicle or CORT 20 mg/kg for 14 days. From 15th to 21st day of treatment, different animals received DVS 10 or 20 mg/kg, ALA 100 or 200 mg/kg or combinations DVS10 + ALA100, DVS20 + ALA100, DVS10 + ALA200 or DVS20 + ALA200. One hour after last administration, animals were subjected to object recognition tests, Y-maze, social interaction and sucrose preference. Twenty-four hours later, animals were decapitated and the brain areas prefrontal cortex (PFC), hippocampus (HC) and striatum (ST) were dissected to measure the levels of Brain Derived Neurotrophic Factor (BDNF). The results showed that treatment with CORT for 21 days caused cognitive impairment, deficit in social interaction and anhedonia-like behavior in animals. In object recognition test, ALA200 and associations of DVS10 with both doses of ALA reversed deficits in short term memory, while DVS20 and associations of ALA200 with both doses of DVS reversed deficits in long-term memory. Already in the Y-maze test, ALA200 and associations of DVS20 with both doses of ALA reversed the deficits caused by CORT in the working memory of the animals. Talking about social interaction, only ALA at both doses was able to reverse the effects of CORT on this behavior. In contrast, treatment with both drugs in monotherapy or associated were effective in improving anhedonia-like behavior when compared with the CORT group. DVS10 alone reversed CORT-induced decrease in BDNF in all brain areas studied. ALA200 achieved this effect in the HC and ST. ALA200 associated to DVS reversed CORT-induced alterations and even, in some cases, increased levels of BDNF when compared to vehicle-treated animals in HC and ST. In compiling, these data show that combination of DVS and ALA proves to be more effective than drug therapy alone. Furthermore, these findings provide subsidies antioxidants for use in the treatment of depressive disorders and support studies that suggest the antidepressant effect of ALA. Coupled to this, our results are apparently promising since combination of conventional therapy with natural antioxidant ALA may possibly reduce the dose of DVS and consequently the side effects of the therapy.